Analisis Pengaruh Sudut Mata Potong Bahan S55C Tipe Flate Terhadap Hasil Cacahan Plastik - Nicola, Adyu Arya; Yudo, Eko; Yunus, Muhammad (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Manage bottle waste in the surrounding environment very important. Therefore, a plastic chopping machine was created which is expected to optimize this problem. One of the most important components in plastic chopping machines is the cutting edge, the cutting edge of the plastic chopping machine plays an important role in the chopping process. The cutting edge used in this study is made from flate-type S55C steel with a cutting edge inclination angle of 25˚ and 35˚. The purpose of this study is to determine the quality of the results of plastic waste shredding against S55C steel cutting edge material, determine the effect of cutting edge angle with angle variations of 25˚ and 35˚ on the results of plastic waste shredding, knowing the angle of the cutting edge that is good for the plastic shredding process. The method used in this research uses experimental methods. The results of this study indicate that the 35˚ angle cutting edge within one minute produces more shreds than the 25˚ angle cutting edge but for the size of the shreds from both cutting edges have the same length and width variations ranging from one to twenty millimeters.